Perbedaan Efektifitas Terapi Seft (Spiritual Emosional Freedom Technique) dan Terapi Musik Keroncong Terhadap Tingkat Depresi pada Lanjut Usia - Etika, Arif Nurma; Haryuni, Sri; Sulistya, Wiwin (Sekolah Tinggi Ilmu Kesehatan Hang Tuah Surabaya, 2017)
Depression is an unfavorable condition for the elderly. When depression goes untreated, elderly can isolate themselves even allowed to end his life. Spiritual Emotional Freedom Technique (SEFT) and Keroncong music allegedly can be used as complementary therapy for elderly depression. This study aimed to determine the difference effect of Spiritual Emotional Freedom Technique (SEFT) and Keroncong music on elderly depression at Jombang geriatric service unit in Pare Kediri. The method used was a quasi-experimental, with a pretest and posttest design. In this study, respondents were grouped into two groups, SEFT intervention group (n=10) and Keroncong music Intervention group (10). In both groups was given four therapy sessions, within four weeks, each session is given therapy for 30 minutes. In this study it was found that the decrease of score depression between pretest and posttest at SEFT therapy (p = 0,008) and keroncong music therapy (p = 0,01). By unpaired t test, posttest obtained, the p value (p=0,760) >0.05 so that there is no significant difference between the posttest score in the SEFT Therapy group and thekeroncong music therapy group. It can be concluded that SEFT and keroncong music reduce depression in elderly, but no more effective between SEFT and keroncong music reduce depression in elderly.Keywords: Depression, Elderly, SEFT, Keroncong Music